An instrumented pulley for field measurements of Torque and Power - Pasikatan, Melchor C.
An instrumental pulley was developed to overcome field problems associated with the conventional method of torque and power measurement. The prototype pulley was machined from mild steel, with spokes serving as strain beams. Strain gages in bridge arrangement attached to the spokes sense the bending stress due to the torque and convert this into millivolt output. Calibration results showed the torque-millivolt relationship was linear, hysterisis and error were less than 1 percent fs. For power instruments, an additional tachometer with de voltage output is necessary. With the tachometer, error in power measurement was +-1.03 W or 0.2 percent fs. Field tests showed its advantages over the calibrated motor method such as, ease of installation, no weight addition relative to the original primeover, portability and safety.